Bulk-like emission in the visible spectrum of colloidal LiYF4:Pr nanocrystals downsized to 10 nm. Issue 14 (5th May 2022) - Komban, Rajesh; Spelthann, Simon; Steinke, Michael; Ristau, Detlev; Ruehl, Axel; Gimmler, Christoph; Weller, Horst
Abstract : Herein, highly stable colloidal LiYF4 :Pr 3+ nanocrystals are presented for the first time. Through extensive comparison of their spectroscopic behavior with bulk crystals an unusual intense bulk like emission in the visible spectrum was observed. Abstract : Though Pr 3+ doped LiYF4 (LiYF4 :Pr 3+ ) bulk crystals are a well-known laser gain material with several radiative transitions, their nanocrystal counterparts have not been investigated with regards to these. Through downsizing to the nanoscale, novel applications are expected, especially in composite photonic devices. For example, nanocrystals in stable colloidal form with narrow size distribution are highly desirable to reduce scattering in such composites. Herein, we synthesized monodispersed LiYF4 :Pr 3+ nanocrystals having a size of 10 nm resulting in colorless clear stable colloidal dispersions and conducted an extensive optical characterization for the first time. We observed unexpected yet intense emission with excited state lifetimes comparable to bulk crystals in the visible spectrum through excitation at 444 nm and 479 nm. In macroscopic bulk crystals, this emission is only exploitable through excitation of a different, subjacent energy level. A comprehensive comparison to the bulk crystals provides deeper insight into the excitation mechanism and performance of these nanocrystals. The presented results pave the way for developing application-oriented LiYF4 :Pr 3+ nanocrystals as emitters with tailored properties for quantum optics or biomedical applications.